Desain didaktis pembelajaran matematika untuk mengatasi hambatan belajar pada materi matriks - Dessy Pangestu Putri; Budi Manfaat; Arif Abdul Haqq (Department of Mathematics Education, UIN Sunan Gunung Djati Bandung, West Java, Indonesia, 2020)
This research is motivated by the emergence of barriers to student learning in matrix. The aims of this research are to formulate didactic matrix material design and find out the results of didactic design implementation in matrix. The method of this research used Design Didactical Research (DDR). There were three stages, namely the didactic situation analysis before learning, the metapedactic analysis, and retrospective analysis. Data collection techniques were interviews, observation, tests and documentation. The subjects of this research were 10th grade students in majoring Banking-1 (X. Perbankan-1) of SMK Negeri 2 Cirebon. This research produces a product in the form of a matrix developed Lesson Plan (RPP) into Student’s Worksheet (LKS). The results of the research showed that the implemented of didactic design can overcome the student learning barriers.